Harmoni Teologi: “Unconditional Election” dan Teologi Kovenan bagi Kehidupan Rohani Jemaat - Daniel Pesah Purwonugroho; Iman Kristina Halawa; Saut Maruli P. Panggabean (DIEGESIS: Jurnal Teologi Kharismatika, 2024)
This article is designed to explore the theological harmony between the doctrine of "unconditional election" and covenant theology and its implications for the spiritual life of the congregation. "Unconditional election" is the concept where God chooses individuals for salvation without regard to their conditions or efforts. Covenant theology frames the interaction between God and humanity through covenants. The harmonization between the doctrine of "unconditional election" and covenant theology centres on the redemptive work and obedience of Jesus Christ on the cross. This obedience of Jesus Christ results in human salvation without any human effort. It also allows humans to experience the covenant of grace without any human effort. Through a qualitative descriptive research method, the theological harmonization between the doctrine of "unconditional election" and covenant theology will be explored to draw spiritual implications for the congregation. The harmonization of "unconditional election" and covenant theology brings individual spiritual well-being and assurance and fosters communal growth.Keywords: harmony; unconditional election; covenant theologyAbstrak Artikel ini dirangkai guna menelusuri harmoni teologi antara doktrin “unconditional election” dengan teologi kovenan dan implikasinya bagi kehidupan rohani jemaat. “Unconditional election” merupakan konsep dimana Allah memilih manusia untuk diselamatkan dan tidak bergantung dengan kondisi dan daya upaya manusia. Teologi kovenan membingkai interaksi Allah dengan manusia melalui kovenan. Harmonisasi antara doktrin “unconditional election” dan teologi kovenan ini bertitik tumpu di dalam karya penebusan dan ketaatan Yesus Kristus di kayu salib. Ketaatan Yesus Kristus ini membawa dampak manusia mengalami keselamatan tanpa melibatkan sedikitpun usaha manusia. Ketaatan Yesus Kristus juga membuat manusia mengalami kovenan anugerah tanpa adanya usaha manusia sedikitpun. Melalui metode penelitian kualitatif deskriptif beserta pengumpulan data studi pustaka, harmonisasi teologi antara doktrin “unconditional election” dan teologi kovenan akan ditelusuri guna menarik implikasi spiritual bagi jemaat. Harmonisasi “unconditional election” dan teologi kovenan membawa jemaat mengalami kesejahteraan dan kepastian spiritual secara individu dan mendatangkan pertumbuhan secara komunal.Kata Kunci: harmoni; unconditional election; teologi kovenan